Sex-speare vs. Shake-speare: On Nudity and Sexuality in Some Screen and Stage Versions of Shakespeare’s Plays - Fabiszak, Jacek (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The article attempts to address the issue of nudity and eroticism in stage and screen versions of Shakespeare’s plays. Elizabethan theatrical conventions and moral and political censorship of the English Renaissance did not allow for an explicit presentation of naked bodies and sexual interactions on stage; rather, these were relegated to the verbal plane, hence the bawdy language Shakespeare employed on many occasions. Conventions play a significant role also in the present-day, post-1960s and post-sexual revolution era, whereby human sexuality in Western culture is not just alluded to, but discussed and presented in an open manner. Consequently, nudity on stage and screen in versions of Shakespeare’s plays has become more marked and outspoken. Indeed, in both filmic and TV productions as well as stage performances directors and actors more and more willingly have exposed human body and sexuality to the viewer/spectator. My aim is to look at such instances from the perspective of realism and realistic conventions that the three media deploy and the effect nudity/sex can have on the recipient. The conclusion is that theatre is most conventional and stark realism and directness of the message need to be carefully dosed. Similarly to the theatre, television, more specifically television theatre, is, too, a most direct genre, as television is inherently a live medium, the broadcasts of which occur here and now, in the present tense (ideally). Film is markedly different from the two previous forms of art: it is narrated in the past tense, thus creating a distance between what is shown and the viewer, and allowing for more literalness. Naturally, particular cases discussed in the article go beyond these rather simple divisions.